Response of Chili (Capsicum annuum L. Var. Cayena) to concentrations of N, P, K, Ca and Mg in Palmira, Valle del Cauca, Colombia - Mejìa de Tafur, Marìa Sara; Martínez Marulanda, Adriana Carolina; Ibarra Espinosa, Dora Mònica; García Dávila, Mario Augusto; Cayon Salinas, Daniel Gerardo (Revista Colombiana de Investigaciones Agroindustriales, 2016)
At the UN (Universidad Nacional de Colombia) was established an experiment to determine the nutritional requirements (N, P, K, Ca and Mg) of chili Capsicum annuum L., with 16 treatments, and 4 replications. 5 samples were staggered at 20, 40, 70, 100 and 140 days after transplantation. The seedlings were established in panels with sterile river sand, and watered with nutrient solutions corresponding to each treatment 20 days after planting (dap) were transplanted to 6 Kg capacity pots using quartz sand as substrate. It was taken as reference the Hoagland and Arnon solution; other treatments were obtained by varying the concentrations of each element. The high concentration corresponds to the control plus 50% of it, the mean concentration, 25% of the high concentration and low, a quarter of the mean concentration. The critical nutrients level was determined by the construction of calibration curves relating the concentration of each nutrient with the biomass accumulation. A parallel line to the X axes was drawn taking as reference 95% of the maximum biomass. The points where the response curve is cut by the parallel are the critical level or adequate concentration range for each nutrient. The adequate concentration for the nutrient solution for cayenne pepper is N 16.2 - 21.5 mmol.L-1. P 1.1 – 1.4 mmol.L-1, and K 4.4 – 8.2 mmol.L-1. No requirements were found for Ca and Mg. Para citar este artículo Martínez,A., Mejía, M., Ibarra, D., García, M. y Cayón, D. (2016). Respuesta del ají (Capsicum annuum L. Var. Cayena) a concentraciones de N, P, K, Ca y Mg en Palmira, Valle Del Cauca, Colombia. Rev. Colomb. Investig. Agroindustriales, 3(1), 40-48. DOI: http://dx.doi.org/10.23850/24220582.419